2023
DOI: 10.3390/fishes8040174
|View full text |Cite
|
Sign up to set email alerts
|

Skin and Blood Microbial Signatures of Sedentary and Migratory Trout (Salmo trutta) of the Kerguelen Islands

Abstract: Our understanding of how microbiome signatures are modulated in wild fish populations remains poorly developed and has, until now, mostly been inferred from studies in commercial and farmed fish populations. Here, for the first time, we have studied changes in the skin and blood microbiomes of the Salmo trutta population of the volcanic Kerguelen archipelago located at the northern limit of the Antarctic Ocean. The Kerguelen Islands present a natural framework of population expansion and reveal a likely situat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…In medicine, the characterization of the peripheral blood-derived microbiome signature, defined as blood microbial DNA, is increasingly used by clinicians to assess an individual's health status, detect dysbiosis and potential pathogens, or as a biomarker to inform disease severity and progression 33 37 . This concept is also gaining momentum in ecology as the circulating microbiome of dogs, bovine, wild birds and wild fish populations were recently studied, showing that the genetic structure of the blood microbiome, just as in humans, is modulated by genetic and spatiotemporal factors, as well as disease conditions 20 , 38 41 . In the present study, the observed shift toward the dominance of Nitrobacter and Sediminibacterium suggests that environmental factors severely impact the blood microbiome signature.…”
Section: Discussionmentioning
confidence: 99%
“…In medicine, the characterization of the peripheral blood-derived microbiome signature, defined as blood microbial DNA, is increasingly used by clinicians to assess an individual's health status, detect dysbiosis and potential pathogens, or as a biomarker to inform disease severity and progression 33 37 . This concept is also gaining momentum in ecology as the circulating microbiome of dogs, bovine, wild birds and wild fish populations were recently studied, showing that the genetic structure of the blood microbiome, just as in humans, is modulated by genetic and spatiotemporal factors, as well as disease conditions 20 , 38 41 . In the present study, the observed shift toward the dominance of Nitrobacter and Sediminibacterium suggests that environmental factors severely impact the blood microbiome signature.…”
Section: Discussionmentioning
confidence: 99%
“…Its high environmental value is explained by the unique wildlife structure, which includes vulnerable species. The remote location of the archipelago-4000 km from South Africa and Australia [69,70]-has created ideal conditions for preserving unique flora and fauna of the Kerguelen Archipelago. The presence of rare Antarctic plant species and high biodiversity is closely linked to the soil developed on the basaltic basement and the specific geological substrate of volcanic origin.…”
Section: Study Areamentioning
confidence: 99%